Effect of Substrates on Nutritional Composition and Functional Properties of Pleurotus Ostreatus - E. G, Mbassi Josiane; Y, Mobou Estelle; A, Ngome Francis; S. L, Sado Kamdem (Current Research in Agricultural Sciences, 2018)
Pleurotus species, commonly known as oyster mushrooms, are edible fungi cultivated worldwide. Pleurotus genus is one of most extensively studied white-rot fungi due to its exceptional ligninolytic properties. These mushrooms have the ability to colonize and degrade a wide variety of lingo-cellulosic wastes with relatively short cycle. The objective of this study was to review published research works on the effect of substrates on nutritional composition and functional property of Pleurotus ostreatus. A literature search was done on the internet and university libraries in this area. It was found that different substrates used in cultivating mushrooms do have effect on the functional, organoleptic and nutritional properties of mushrooms. This review presents a practical checklist of effect of substrates on quality of Pleurotus ostreatus that may help different users.